2011
DOI: 10.3139/217.2437
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Gas Counter Pressure Technology and Its Application to Improve the Surface Quality of Microcellular Injection Molded Parts

Abstract: The purpose of this study is to establish the Gas Counter Pressure (GCP) technology in combined with microcellular injection molding process. The application of gas into the mold cavity during the melt injection period provides a counter force against the melt front advancement, restricting the foaming process during the melt filling stage. Various gas counter pressures from 0 bar up to 300 bar and gas holding times of 0 to 10 s after filling completion were employed for investigating their relevant effect. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…79 Also, the investigation demonstrated that by combining both GCP and elevated mould temperatures, an increase in both the surface quality and cellular morphology can be achieved. 79 The results obtained by Chen et al 80 also proved that GCP is effective at reducing surface defects. In particular, when processing a PS polymer, a surface roughness improvement of more than 90% was achieved.…”
Section: Gas Counter Pressurementioning
confidence: 91%
See 1 more Smart Citation
“…79 Also, the investigation demonstrated that by combining both GCP and elevated mould temperatures, an increase in both the surface quality and cellular morphology can be achieved. 79 The results obtained by Chen et al 80 also proved that GCP is effective at reducing surface defects. In particular, when processing a PS polymer, a surface roughness improvement of more than 90% was achieved.…”
Section: Gas Counter Pressurementioning
confidence: 91%
“…Furthermore, it was found that when applying a holding time of 10 s, the parts exhibited no foaming until the melt is solidified. 80 Lee et al 81 proposed a combination of both GCP and core-back processing with high density PE (HDPE). to produce Class A surface finishes.…”
Section: Gas Counter Pressurementioning
confidence: 99%
“…When the gas counter pressure is greater than the critical pressure, then the melt may retain as a single phase without any foaming as long as the counter pressure applies. Recently, a more detailed study of the surface quality of microcellular injection molded parts was investigated using GCP technology [24]. It was found that when the GCP is greater than a certain value, a foaming free part surface can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Gas Counter Pressure (GCP) technique consists of pressurizing to a high pressure the mold cavity, allowing filling by the polymer/gas system but restricting foaming, as pressure drop does not occur [109]. Thus, fracture cells on the melt flow front is inhibited and swirl marks are eliminated.…”
Section: Gas Counter Pressurementioning
confidence: 99%